Effectiveness of Educational videos and Games for the Concept Clarity and Understanding of Social Studies Subject: An Intervention Study - Farhana Khurshid, Maria Bibi, (PJE, 2023)
Information and Communication Technology (ICT) is considered as a key requirement for learners because it augments their learning. This study investigated the effectiveness of utilising educational videos and games into teaching for better understanding and concept clarity of students in the subject of Social Studies. This experimental study was conducted in two government secondary schools, for four weeks on a sample size of fifty-eight students of 8th class. Different topics from Social Studies subject were taught to the sample with the help of educational videos and games